BaNb0.05Fe0.95O3−δ as a new oxygen reduction electrocatalyst for intermediate temperature solid oxide fuel cells - Dong, F.; Chen, Y.; Ran, R.; Chen, D.; Tade, Moses; Liu, Shaomin; Shao, Zongping (R S C Publications, 2013)
Cobalt-free perovskite BaNb0.05Fe0.95O3−δ (BNF) is synthesized and characterized towards application as a cathode material for intermediate temperature solid oxide fuel cells. In situ X-ray diffraction and transmission electron microscopy are applied to study the crystal structure and thermally induced phase transformation. BNF exists as a multiphase structure composed of a monoclinic phase and a cubic phase at room temperature, and then undergoes a phase transformation to a cubic structure starting at ~400°C, which is maintained at temperatures up to 900°C during a thermal cycle between room temperature and 900°C; while it retains the cubic perovskite lattice structure on cooling from 900°C to room temperature. Oxygen temperature-programmed desorption, combined thermal expansion and thermo-gravimetric analysis are used to clarify the thermal reducibility of BNF. A relatively good stability of BNF is demonstrated by electrical conductivity and electrochemical impedance spectroscopy measurements. The activity of BNF for oxygen reduction reaction is probed by symmetrical cell and single fuel cell tests. Favorable electrochemical activities at intermediate temperature, e.g. very low interfacial resistance of only ~0.016 ohm cm-2 and maximum power density of 1162 mW cm-2 at 750°C, are demonstrated, which could be attributed to the cubic lattice structure of BNF within the temperature range of cell operation.